On the modulation of TRPM channels: Current perspectives and anticancer therapeutic implications - Ciaglia, Tania; Vestuto, Vincenzo; Bertamino, Alessia; González-Muñiz, Rosario; Gómez-Monterrey, Isabel (Frontiers in Oncology, 2023)
The transient receptor potential melastatin-subfamily (TRPM) ion channels regulate ion homeostasis and function as cellular sensors and transducers of important biological signal pathways. TRPMs are aberrantly expressed in various solid malignancies, and this overexpression correlates with tumor progression. Dependent on cancer type, experimental data have revealed important roles for TRPM channels in cancer cell proliferation, survival, and invasion. Recent reports also reveal the mechanisms that mediate the biological roles of TRPM in tumor epithelial-mesenchymal transition (EMT), autophagy, and cancer metabolic reprogramming. These implications make TRPM proteins putative targets for new therapeutic approaches. Here, we discussed the main characteristics of all members of the TRPM family, focusing on the current knowledge about the connection between TRPM channels and critical cancer hallmarks. We also cover TRPM modulators used as pharmaceutical tools in biological assays, and an indication of molecules that have reached clinical trials. To conclude, the authors outline the prospects for TRPM channels in the oncological field.